2014
DOI: 10.3384/diss.diva-105872
|View full text |Cite
|
Sign up to set email alerts
|

Deliberations on the impact of antibiotic contamination on dissemination of antibiotic resistance genes in aquatic environments

Abstract: The great success of antibiotics in treating bacterial infectious diseases has been hampered by the increasing prevalence of antibiotic resistant bacteria. Not only does antibiotic resistance threaten to increase the difficulty in treating bacterial infectious diseases, but it could also make medical procedures such as routine surgery and organ transplantations very dangerous to perform. Traditionally, antibiotic resistance has been regarded as a strictly clinical problem and studies of the problem have mostly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 154 publications
(283 reference statements)
0
9
0
Order By: Relevance
“…Vancomycin-resistant S. aureus (VRSA) is emerging rapidly in the environment since 1996 and, this has been highlighted in studies conducted by Lowy (2003) and Berglund (2014). In some cases, these strains might be MRSA and they are fully resistant to vancomycin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Vancomycin-resistant S. aureus (VRSA) is emerging rapidly in the environment since 1996 and, this has been highlighted in studies conducted by Lowy (2003) and Berglund (2014). In some cases, these strains might be MRSA and they are fully resistant to vancomycin.…”
Section: Resultsmentioning
confidence: 99%
“…Genes transfer can also occur through bacteriophage. It was reported that mecA gene encoded for the methicillin resistance in MRSA was found in the DNA of the bacteriophage (Colomer-Lluch et al, 2011;Berglund, 2014) through the transduction process. Bacteriophage acts as vehicles for antibiotic resistance genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations